Age, sex and ethnic differentials in the prevalence and control of epilepsy among Sri Lankan children: a population-based study - Jithangi Wanigasinghe; Carukshi Arambepola; Roshini Murugupillai; Thashi Chang (BMJ Paediatrics Open)
Objective To estimate the prevalence of childhood epilepsy in Sri Lanka by different age groups (0–5, 6–10 and 11–16 years), sex and ethnicity, and to describe the types and outcomes of epilepsy.Design and patients A population-based, cross-sectional study was conducted in the district considered to be ethnically most balanced in Sri Lanka. A door-to-door survey was performed in the 0–5 year age group (60 geographically defined areas as clusters; 19 children per cluster), and a school-based survey in the 6–16 year age group (150 classes as clusters; 25 children per cluster). The screened children with epilepsy were reviewed individually for confirmation of the diagnosis of epilepsy, typing of the underlying epilepsy syndrome and assessment of control. The same group of children were re-evaluated 1 year later to reconfirm the syndromic diagnosis and to assess the stability of control of epilepsy.Results The overall prevalence of childhood epilepsy was 5.7 per 10 000 children aged 0–16 years (95% CI: 38 to 87). It was higher with younger ages (73.4 per 10 000 children aged 0–5 years; 55.1 per 10 000 children aged 6–10 years and 50.4 per 10 000 children aged 11–16 years). A male dominance was noted in both age groups. In each age group, the prevalence was highest in children of Sinhalese ethnicity. Symptomatic focal epilepsy was the single most common group of epilepsy in both age groups. Majority of children remained well controlled on medications.Conclusion The findings indicate a relatively high burden of epilepsy among children in Sri Lanka, however, these were comparable to the burden of disease reported from other countries in the region.